Philippine taxation laws (Quezon City, Philippines : Central Book Supply, 2021)
It is a compilation of basic laws on the subject of Taxation. It contains provisions of the 1987 Constitution that refers to taxation, the National Internal Revenue Code of 1997, and its latest amendments, provisions of the Local Government Code on local and real property taxation.
I. Organization and function of the Bureau of Internal Revenue -- II. Tax on Income -- III. Estate and Donor's taxes -- IV. Value Added Tax -- V. Other percentage taxes -- VI. Excise Taxes on certain goods and services. -- VII. Documentary Stamp Tax -- VIII. Remedies -- IX. Compliance Requirements -- X. Statutory offenses and penalties -- XI. Allotment of Internal revenue -- XII. Oversight Committee -- XIII. Tax Incentives -- XIV. Repealing Provisions -- Xv. Final Provisions.
Keywords: TAXATION -- LAW AND LEGISLATION -- PHILIPPINES